Improvement of the bladder perfusion curative effect through tight junction protein degradation induced by magnetic temperature-sensitive hydrogels - Sun, Xiaoliang; Song, Xinhong; Guo, Peng; Zhang, Dong; Zuo, Shishuai; Leng, Kang; Liu, Yun; Zhang, Haiyang (Frontiers in Bioengineering and Biotechnology, 2022)
Postoperative intravesical instillation of chemotherapy is a routine procedure for non-muscular invasive bladder cancer (NMIBC). However, traditional bladder perfusion methods have insufficient exposure time, resulting in unsatisfactory therapeutic effects. In the present study, a chitosan (CS)-based in situ forming depot (ISFD) delivery system, including Fe3O4 magnetic nanoparticles (Fe3O4-MNP), CS, and β-glycerophosphate (GP) as main components, was synthesized. Pirarubicin (THP), as a chemotherapeutic drug, was loaded into the new system. Results showed that our carrier system (Fe3O4-THP-CS/GP) was converted into gel and attached to the bladder wall, possessing loose network structures with magnetic targeting and sustained release properties. Moreover, its retention time in bladder was more than 72 h accompanied by a suitable expansion rate and good degradation characteristics. The antitumor activities of Fe3O4-THP-CS/GP were more effective both in vitro and in vivo than the free THP solution. In the study of its mechanism, results showed that Fe3O4-THP-CS/GP suppressed the expression of occludin (OCLN) and affected tight junctions (TJ) between urothelial cells to promote THP absorption.